STRATEGI PEMBELAJARAN AL-QURAN PADA LEMBAGA MAJELIS AL-QURRA’ WA AL-HUFFAZ PONDOK PESANTREN AS’ADIYAH SENGKANG KABUPATEN WAJO - Hasyim, Wahid (Inspiratif Pendidikan, 2017)
The main problem of this research is how is the learning strategy of Alquran at Al-Qurra ’wa Al-Huffaz boarding school boarding board of As’adiyah Sengkang Wajo Regency? The subject matter is divided into three sub-problems or research questions are: 1) How to describe the strategy of memorating the Qur’an to the institution of Al-Qurra ’wa Al-Huffaz boarding school boarding As’adiyah Sengkang Wajo Regency ?, 2) How the institution’s efforts in improving the learning strategy The Qur’an in the institution of Al-Qurra ’wa Al-Huffaz boarding boarding school As’adiyah Sengkang Wajo Regency This type of research is a qualitative research / field research with research approach used is sociological, theological, pedagogical and psychological approach. The source of research data obtained directly muhafizd, santri and alumni. Further data collection methods used are interview observation, and documentation and tracing of various literature or references. Then the technique of processing and data analysis is done through three stages, namely data reduction, presentation, and conclusion. The results of this research indicate that: 1) the strategy of memorizing the Qur’an in the institution of Al-Qurra ’wa Al-Huffaz boarding boarding school As’adiyah Sengkang Wajo District covers the selection stage, fostering tajwid, standardization of memorization of Qur’an, the pattern of rote settings and maddarasa system fatappulo seddi continuously and stage mappanre temme 2) efforts made by the institution in improving the strategy of memorizing the Qur’an to the institution of Al-Qurra ’wa Al-Huffaz boarding boarding school As’adiyah Sengkang Wajo District includes strengthening of discipline, fostering recitations and fasahah, , gradually building dormitories, holding regular hifdzil qur’an contests as well as the wisdom of pesantren to join the hafizd who have already attended the equation test. The implication of this research is that it is hoped that this research can become one of the academic contribution for all people who want to learn the pattern of strategy of Quranic memorizing effectively and efficiently both in terms of curriculum of tahfidz institution, personal, and for massive dissemination.